Effect of Sodium in LiNi0,5Mn0,3Co0,2O2 as a Lithium Ion Battery Cathode Material by Solid State Reaction Method - Yustinus Purwamargapratala; Indra Gunawan; Evvy Kartini; Anne Zulfia; Alexey Glushshenkov; D.N. Haerani; Sudirman Sudirman (Green Engineering Society, 2022)
Abstract. Lithium-ion batteries (LIBs) have become widely used powder sources for portable electronics and electric vehicles. The discovery of lithium nickel manganese cobalt oxide (LiNi0.5Mn0.3Co0.2O2, NMC532), tremendous efforts have been paid to the development of Ni-rich layer-structured NMC532 materials due to its high capacity when charged to potentials higher than 4.3 V vs Li+/Li. In this work we report effect of Sodidium in NMC532 layer, the characterization was done by using X-Ray Diffractometer (XRD) to investigate the crystal structure, Electrochemical impedance spectroscopy (EIS) was used to illustrate the resistance change during cycling. The particles morphology and surface chemistry characterizations of both cathode and anode electrodes were performed on Scanning Electron Microscope (SEM). The XRD pattern of the sample shows diffraction peaks at 2θ = 18.663 o, 36.773 o, 44.459 o, 48.611 o, 58.604 o, 64.322 o, 65.069 o, 68.339 o and 77.798 o. Na does not affect the NMC532 lattice parameters, which means that Na which is expected to substitute for Li does not occur. The NMC532 conductivity with the addition of Na=0.03 showed a slightly lower value than the NMC532 conductivity with the addition of Na=0.01. Meanwhile, the highest conductivity was seen at NMC532 with the addition of Na=0.05. The addition of Na to NMC532 did not increase the conductivity linearly. SEM images of NMC532 and NMC532 with the addition of Na=0.01; Na = 0.03 and Na = 0.05 can be seen that the Na flakes wrap around the NMC532 granules. The Na flakes surrounding the NMC532 grains at Na = 0.01 were more abundant than the Na flakes surrounding the NMC532 at Na = 0.03.